Danza folclórica fluminense y el turismo cultural en el cantón Palenque Provincia de Los Ríos - Ibarra Macias, Kenia Carolina (2020)
The diverse traditional folkloric manifestations that are part of the Identity and Heritage of a community, originating from each of the country's regions, can be considered as cultural, artistic expressions, prevailing as a witness of the identity of the Indigenous Peoples and Nationalities of Ecuador, the Folk Dance emphasizes the artistic, musical, and corporal representation that manifests the authentic expressions of the Customs and Traditions of Montubio Fluminense. Currently, the folkloric artistic manifestations represent the Intangible Cultural Heritage, begin minimized as a tourist attraction in certain places, it is of vital importance to mention that the traditions and ancestral customs are the contribution in the culture worldwide and must be strengthened so that they remain in future generations. It is important to state that this research has as its main objective to analyze the importance of Folk Dance as a Cultural Tourist resource in the Palenque Canton of the Los Ríos province, rescuing traditions, ancestral knowledge, and the distinctive Cultural Identity of the Montubio people, contributing to the socio-economic development in the Palequeña population, receiving local and national tourists. In this case study, the beneficiaries that have a direct impact is the Palenqueña locality, awakening interest in the population and encouraging them to know and preserve the importance of the indigenous traditions and customs that differentiate and identify the Montubio people of the Los Ríos Province.